Pengaruh Variasi mAs terhadap Densitas pada Hasil Radiograf Os Femur - Cipta Ismaya Rahman; Aulia Annisa; Muhammad Firdaus (Poltekkes Kemenkes Semarang, 2024)
Background: The human body's anatomical structure may be seen in radiological image findings. The proper exposure factor must be given in order to produce radiographic findings. The amperage value times the exposure period is equal to mAs. A darker image will result from a larger mA factor or longer exposure time. However, by choosing the appropriate exposure factor, an optimal radiograph density can be produced that can clearly display the difference in thickness and density between organs. The purpose of this study is to determine the results of how density affects the results of radiographs of the os femur.Methods: This research is quantitative using experimental methods to find out how the effect of mAs variations and how much the range of changes in value on density in AP projection femur examinations using mAs variations namely mAs 4, 8, 10, 12, 20, 25, and 32 with a fixed kV of 70 kV.Results: The results of this study indicate that there is a change in the effect of density quality on the variation of mAs on the radiograph results of the femoral os using the Friedman test p-value 0.001 which means less than 0.05. And the range of changes in density values at the caput femur, collum femur, collum femur, and greater trochanter there are changes in each mAs variation. The value of density variation against 7 mAs variations in radiograph results at variations of 4 to 32 mAs shows the density value increases by 0.14, for the range of increase in each variation it is ± from 0.02 to 0.05.Conclusions: The purpose of this study is to determine the results of how density is affected and the results of how the range of changes in density values on femur radiographs.